(untitled) (Eurasian Scientific Herald, 2024)
Today, the demand for beekeeping in Uzbekistan and maintaining rational specialization in the production of honey and bee products (wax, propolis, pollen (perga), bee milk, nec tar, wax products), which are its medicinal products, is the daily market of our independent republic. It forms the basis of our economy in the transition period. In order to develop the beekeeping sector and increase the productivity of the bee family in the conditions of Uzbekistan, beekeepers are given a firm task to increase the production of honey and bee products at the expense of increasing the productivity of each bee family. For this purpose, it is necessary to grow and buy bees adapted to climatic conditions in regions from early spring